2008
DOI: 10.1080/13527260701856657
|View full text |Cite
|
Sign up to set email alerts
|

Do different industries report Corporate Social Responsibility differently? An investigation through the lens of stakeholder theory

Abstract: The social responsibility of business has become a major issue in recent years and the reporting of such activity is becoming more prevalent. Companies are attuning to the benefits of being seen as socially responsibly and many industries are jumping on the bandwagon of reporting CSR and using different media to communicate their activities in this arena to their stakeholders. This paper considers the content of one type of such communications, the annual report, and looks at how organisations are taking a foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
199
3
19

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(250 citation statements)
references
References 56 publications
12
199
3
19
Order By: Relevance
“…Consistent with earlier work (e.g. see Sweeney and Coughlan, 2008;Holder-Webb et al, 2009;Morhardt, 2010), our assessment further confirms noticeable variation across sectors regarding their propensity to disclose non-financial information. More comprehensive environmental disclosures by industrial firms have been also identified in the recent studies of Liu and Anbumozhi (2009), da Silva Monteiro and Aibar-Guzmán (2010) Andrikopoulos and Kriklani (2012).…”
Section: Discussion -Managerial Relevancesupporting
confidence: 79%
“…Consistent with earlier work (e.g. see Sweeney and Coughlan, 2008;Holder-Webb et al, 2009;Morhardt, 2010), our assessment further confirms noticeable variation across sectors regarding their propensity to disclose non-financial information. More comprehensive environmental disclosures by industrial firms have been also identified in the recent studies of Liu and Anbumozhi (2009), da Silva Monteiro and Aibar-Guzmán (2010) Andrikopoulos and Kriklani (2012).…”
Section: Discussion -Managerial Relevancesupporting
confidence: 79%
“…This technique has been widely employed in CSR research, and is the most common method of analysing social and environmental disclosure by firms (Gray et al, 1995;Milne and Adler, 1999). Content analysis is, at its simplest, a research technique used to determine the presence of certain words or concepts within a passage of text (Sweeney and Coughlan, 2008). In line with the methodological recommendations of Gray et al (1995), and given that a prerequisite for any research is some definition of the subject to be researched, we adopted the broad definition of sport as outlined in the Council of Europe's European Sports Charter (1992), where "sport means all forms of physical activity which, through casual or organised participation, aims at improving physical fitness and mental well-being, forming social relationships, or obtaining results in competition at all levels".…”
Section: Methodsmentioning
confidence: 99%
“…More recent study identified significant difference between how organisations in different industry sectors communicate CSR through two distinct media: the web and annual reports (Sweeney and Coughan, 2008). There is also evidence that the country of origin of the corporation exercises an influence over CSR communication on the web, at least when companies in the oil industry were analysed for a comparative study between UK and Brazil (Farache et al, 2007a).…”
mentioning
confidence: 99%